Transparent near-infrared perovskite light-emitting diodes - Xie, Chenchao (Nat Commun, 2020)
Mobile and wearable devices are increasingly reliant on near-infrared (NIR) covert illumination for facial recognition, eye-tracking or motion and depth sensing functions. However, these small devices offer limited spatial real estate that is typically already occupied by their full-area electronic color displays. Here, we report a transparent perovskite light-emitting diode (LED) that could be overlaid across a color display to provide an efficient and high-intensity NIR illumination. Our transparent devices are constructed with an ITO/AZO/PEIE/FAPbI(3)/poly-TPD/MoO(3)/Al/ITO/Ag/ITO architecture, and offer a high average transmittance of more than 55% across the visible spectral region. In particular, our Al/ITO/Ag/ITO top transparent electrode was designed to offer a combination low sheet resistance and low plasma damage upon electrode deposition. The devices emit at 799 nm with a high total external quantum efficiency of 5.7% at a current density of 5.3 mA cm(−2) and a high radiance of 1.5 W sr(−1) m(−2), and possess a large functional device area of 120 mm(2). The efficient performance is ideal for battery-powered wearable devices, and could enable advanced security and sensing features on future smart-watches, phones, gaming consoles and augmented or virtual reality headsets.